ENHANCING RELEVANCE IN EDUCATION THROUGH A CONTEXTUALLY DESIGNED CURRICULUM - Mbogo, Rosemary Wahu (Advances in Social Sciences Research Journal, 2018)
The ever-changing needs of students, teachers and other education stakeholders as well as the needs in the job market necessitates having a responsive curriculum that bridges the knowledge gap and contextual realities of the world today. Despite the widely acknowledged importance of a contextually relevant curriculum design, its implementation remains a challenge in many learning institutions in Kenya. This paper is a review on designing a contextual curriculum that is relevant to the education system in Kenya. The paper thus explores the development of a contextually relevant curriculum (CRC); identifying various contextual considerations for its design, explaining the dynamics in developing CRC, and describing the how to develop and evaluate a CRC.